Release film used for manufacturing membrane-electrode assembly
The release film, featuring a polyester substrate and an atactic polystyrene release layer, addresses adhesion and wettability issues in membrane electrode assembly manufacturing, thereby enhancing productivity and preventing unintended peeling.
Patent Information
- Application Number
- JP2023172951
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-10-04
AI Technical Summary
Existing release films for membrane electrode assembly manufacturing suffer from insufficient wettability, adhesion issues, and a tendency to cause unintended peeling of the ion exchange resin layer, leading to productivity challenges.
A release film comprising a polyester substrate layer and a release layer made of atactic polystyrene, which provides excellent adhesion, wettability, and prevents unintended peeling during the manufacturing process of membrane electrode assemblies.
The proposed release film effectively prevents unintended peeling of the ion exchange resin layer, enhances wettability, and contributes to improved productivity in the manufacturing of membrane electrode assemblies.
Smart Images

Figure 2025063601000001_ABST
Abstract
Description
[Technical field]
[0001] The present specification discloses a release film used in a process for producing a membrane electrode assembly, which is a component of a polymer electrolyte fuel cell. The present specification further discloses a method for producing the membrane electrode assembly. [Background technology]
[0002] A solid polymer electrolyte fuel cell has a membrane electrode assembly. The membrane electrode assembly includes a solid polymer electrolyte membrane and two catalyst layers. Each catalyst layer is bonded to a surface of the electrolyte membrane. Both the electrolyte membrane and the catalyst layers are ion exchange resin layers.
[0003] In the manufacture of a membrane electrode assembly, an electrolyte membrane is formed on a first release film, and a catalyst layer is formed on a second release film. The catalyst layer is brought into contact with the electrolyte membrane. The electrolyte membrane and the catalyst layer are heated and pressurized to bond the catalyst layer to the electrolyte membrane. The first release film is then peeled off from the electrolyte membrane. The first release film is required to have appropriate adhesion to the electrolyte membrane and appropriate releasability. The second release film is peeled off from the catalyst layer. The second release film is required to have appropriate adhesion to the catalyst layer and appropriate releasability.
[0004] JP 2014-154273 A discloses a release film having a base layer and a release layer. The base layer is made of polyethylene terephthalate. The surface of the base layer is smooth. Therefore, the release film can contribute to the long life of the membrane electrode assembly.
[0005] JP 2014-175116 A discloses a release film in which the material of the release layer is syndiotactic polystyrene. This release film has excellent releasability to an ion-exchange resin layer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP2014-154273A [Patent Document 2] JP2014-175116A Summary of the Invention [Problem to be solved by the invention]
[0007] A laminate is obtained by bonding the back side of the ion exchange resin layer to the front side of the release film disclosed in JP 2014-154273 A. The laminate is wound on a reel. By winding, the front side of the ion exchange resin layer comes into contact with the back side of the release film of a different rotation. Since the base layer is smooth, the front side of the ion exchange resin layer can be in close contact with the back side of the release film. Due to this close contact, when the laminate is unwound from the reel, the ion exchange resin layer is pulled by the release film of a different rotation. This can cause the back side of the ion exchange resin layer to be unintentionally peeled off from the front side of the release film of the same rotation. This phenomenon is called blocking.
[0008] The release film disclosed in JP 2014-154273 A has insufficient wettability on the front side surface. In particular, when an aqueous or water-rich coating liquid is used for the ion exchange resin layer, there is a strong demand for improving the wettability.
[0009] The release film disclosed in JP 2014-175116 A has high solvent resistance because the material of the release layer is syndiotactic polystyrene. With this release film, it is difficult to apply a coating liquid for the ion exchange resin layer. If the material of the release layer is syndiotactic polystyrene, which has a low molecular weight, coating can be performed. However, the use of this polystyrene causes defects such as curling and fish eyes in the release film.
[0010] The release film disclosed in JP 2014-175116 A has insufficient adhesion to the ion-exchange resin layer, and therefore, unintended peeling of the ion-exchange resin layer from the release film may occur during the manufacturing process of the membrane electrode assembly.
[0011] The applicant's intention is to provide a release film which is less susceptible to unintended peeling of an ion-exchange resin layer, has excellent wettability, and can contribute to the productivity of membrane-electrode assemblies. [Means for solving the problem]
[0012] The release film disclosed in the present specification can be used in the manufacture of a membrane electrode assembly. The release film has a base layer and a release layer laminated on the base layer. The main material of the base layer is polyester. The release layer contains atactic polystyrene. Effect of the Invention
[0013] The release film can suppress unintended peeling of the ion-exchange resin layer. The release film has excellent wettability. Furthermore, the release film can contribute to the productivity of the membrane electrode assembly. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a cross-sectional view showing a part of a release film according to one embodiment. [Diagram 2] FIG. 2 is a flow chart showing a method for producing a membrane electrode assembly in which the release film of FIG. 1 is used. [Diagram 3] FIG. 3 is a schematic diagram showing an example of a process of the manufacturing method of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Preferred embodiments will be described below with reference to the drawings as appropriate. Each configuration and their combination in each embodiment is an example. Modifications such as omission and substitution of configurations in the embodiments are possible within the scope of the present disclosure, and other configurations can also be added to the embodiments. The scope of disclosure of this specification is not to be interpreted as being limited by the embodiments. Each aspect disclosed in this specification may be combined with any other feature disclosed in this specification.
[0016] [Release film] 1 shows a release film 2. The release film 2 has a base layer 4 and a release layer 6. The release layer 6 is laminated to the base layer 4. The base layer 4 has a back side 8 and a front side 10. The release layer 6 has a back side 12 and a front side 14. The release film 2 may have other layers located between the base layer 4 and the release layer 6.
[0017] [Base material layer] A typical material of the base material layer 4 is polyester. As described later, the release film 2 is used in the manufacturing process of a membrane electrode assembly. In this manufacturing process, the temperature of the release film 2 increases. Furthermore, tension is applied to this release film 2 in the manufacturing process. The base material layer 4 made of polyester is unlikely to stretch even when tension is applied in a high-temperature environment. This base material layer 4 can suppress the stretching of the release film 2 in the manufacturing process of the membrane electrode assembly. The release film 2 that is unlikely to stretch can suppress unintended peeling of the electrolyte membrane or catalyst layer, described later, in the manufacturing process of the membrane electrode assembly.
[0018] The base layer 4 may contain a combination of polyester and other resin. In this case, the ratio of polyester to the total amount of resin is 50% by mass or more. In other words, the main material of the base layer 4 is polyester. The ratio of polyester is more preferably 70% by mass or more, and particularly preferably 80% by mass or more. This ratio may be 100% by mass. The material of the base layer 4 may be a composition containing a resin and an additive.
[0019] Preferred polyesters include polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate and polybutylene naphthalate, with polyethylene terephthalate and polyethylene naphthalate being more preferred, and polyethylene terephthalate being particularly preferred.
[0020] A preferred base layer 4 from the viewpoint of suppressing elongation of the release film 2 is a stretched film. A uniaxially stretched film and a biaxially stretched film can be used as the base layer 4. From the viewpoint of strength, a biaxially stretched film is preferred. Each of the longitudinal stretching ratio and the transverse stretching ratio in the biaxially stretched film is preferably 1.5 or more, more preferably 2.5 or more, and particularly preferably 3.0 or more.
[0021] The average roughness Sa of the substrate layer 4 is preferably 20 nm or less. In other words, the surface of the substrate layer 4 has excellent smoothness. As described later, the release layer 6 is thin. Therefore, the surface state of the release layer 6 can reflect the surface state of the substrate layer 4. The substrate layer 4 having excellent surface smoothness can achieve the release layer 6 having excellent surface smoothness. As described later, the release layer 6 can contribute to a long life of the membrane electrode assembly. From the viewpoint of a long life of the membrane electrode assembly, the average roughness Sa of the substrate layer 4 is more preferably 15 nm or less, and particularly preferably 13 nm or less. The lower limit of the average roughness Sa that can be achieved is 1 nm.
[0022] As shown in Fig. 1, the front side 10 of the base layer 4 is covered with a release layer 6. Therefore, the average roughness Sa is measured on the rear side 8. A suitable device for the measurement is a non-contact surface shape measurement system ("VertScan2.0", Ryoka Systems Co., Ltd.). The measurement conditions are as follows: Mode: WAVE Objective lens magnification: 5x 0.5×Tube lens
[0023] In FIG. 1, an arrow T1 indicates the thickness of the base material layer 4. The thickness T1 is preferably 1 μm or more and 300 μm or less. The base material layer 4 having a thickness T1 of 1 μm or more can suppress the elongation of the release film 2 in the manufacturing process of the membrane electrode assembly. From this viewpoint, the thickness T1 is more preferably 10 μm or more, and particularly preferably 20 μm or more. The base material layer 4 having a thickness T1 of 300 μm or less does not inhibit the productivity of the membrane electrode assembly. From this viewpoint, the thickness T1 is more preferably 200 μm or less, and particularly preferably 100 μm or less.
[0024] [Release layer] The release layer 6 is a resin film. A suitable resin for the release layer 6 is atactic polystyrene. As described later, in the manufacturing process of the membrane electrode assembly, an electrolyte membrane is formed on the release film 2. The release film 2 needs to have adhesion to this electrolyte membrane. In the manufacturing process of the membrane electrode assembly, a catalyst layer is also formed on the release film 2. The release film 2 needs to have adhesion to the catalyst layer. The release layer 6 is in direct contact with the electrolyte membrane or the catalyst layer. The release layer 6, whose material is atactic polystyrene, can contribute to adhesion to the electrolyte membrane and the catalyst layer.
[0025] Atactic polystyrene is amorphous. Atactic polystyrene resin can be obtained by radical polymerization of aromatic vinyl monomers. Examples of aromatic vinyl monomers include styrene; alkyl-substituted styrenes such as o-methylstyrene, m-methylstyrene, p-methylstyrene, vinylxylene, p-ethylstyrene, p-isopropylstyrene, butylstyrene, pt-butylstyrene, and 2,4-dimethylstyrene; alkoxy-substituted styrenes such as methoxystyrene and ethoxystyrene; halogen-substituted styrenes such as o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, o-bromostyrene, and o-fluorostyrene; α-alkyl-substituted styrenes; aryl-substituted styrenes; and vinylnaphthalene. Atactic polystyrene may be obtained from two or more monomers. The release layer 6 may contain two or more atactic polystyrenes.
[0026] From the viewpoint of heat resistance of the release layer 6, the weight average molecular weight of the atactic polystyrene is preferably 10,000 or more, more preferably 100,000 or more, and particularly preferably 150,000 or more. From the viewpoint of ease of production, the weight average molecular weight is preferably 1,000,000 or less, more preferably 500,000 or less, and particularly preferably 350,000 or less. The weight average molecular weight is measured in terms of polystyrene by gel permeation chromatography.
[0027] The material of the release layer 6 may be a composition containing atactic polystyrene resin and additives. The material of the release layer 6 may be a composition containing atactic polystyrene and other resins. The material of the release layer 6 may be a composition containing atactic polystyrene, other resins and additives. In either composition, the ratio of atactic polystyrene to the total amount of resin is preferably 50% by mass or more. In other words, it is preferable that the main material of the release layer 6 is atactic polystyrene. The ratio of atactic polystyrene is more preferably 70% by mass or more, and particularly preferably 80% by mass or more. This ratio may be 100% by mass.
[0028] Examples of additives that can be included in the composition of the release layer 6 include fillers, lubricants such as wax, fatty acid esters, and fatty acid amides, antistatic agents, stabilizers such as antioxidants, heat stabilizers, and light stabilizers, flame retardants, viscosity modifiers, thickeners, and defoamers. The composition may include organic or inorganic particles.
[0029] The water contact angle of the surface of the release layer 6 is preferably 92° or less. A release film 2 having a water contact angle of 92° or less has excellent adhesion to the ion exchange resin layer. From this viewpoint, the water contact angle is more preferably 90° or less, and particularly preferably 89° or less. As shown in FIG. 1, the back surface 12 of the release layer 6 overlaps with the base layer 4. Therefore, the water contact angle is measured at the front surface 14. Atactic polystyrene can contribute to the small water contact angle.
[0030] In FIG. 1, an arrow T2 indicates the thickness of the release layer 6. The thickness T2 is preferably 0.1 μm or more and 20 μm or less. The release layer 6 having a thickness T2 of 0.1 μm or more can be sufficiently adhered to the base layer 4. From this viewpoint, the thickness T2 is more preferably 0.3 μm or more, and particularly preferably 0.5 μm or more. The release layer 6 having a thickness T2 of 20 μm or less does not inhibit the productivity of the membrane electrode assembly. From this viewpoint, the thickness T2 is more preferably 10 μm or less, and particularly preferably 5 μm or less.
[0031] [Thickness ratio] The ratio (T2 / T1) of the thickness T2 of the release layer 6 to the thickness T1 of the base layer 4 is preferably 5 / 1 to 1 / 10, more preferably 3 / 1 to 1 / 5, and particularly preferably 2 / 1 to 1 / 3.
[0032] [Release film manufacturing method] Examples of the method for laminating the release layer 6 to the base layer 4 include a coating method, a coextrusion method, an extrusion lamination method, a pressure bonding method, and an adhesive method. In terms of smoothness of the release layer 6, the coating method is preferred. In the coating method, a solution or dispersion containing atactic polystyrene is coated on the base layer 4. Examples of the solvent for the solution or dispersion include aromatic hydrocarbons such as benzene, toluene, and xylene; alicyclic hydrocarbons such as cyclohexane, cyclohexanone, and cyclohexene; halogenated hydrocarbons such as dichloromethane and dichloroethane; cyclic amides such as N-methyl-2-pyrrolidone; and cyclic ethers such as dioxane. Two or more solvents may be used in combination.
[0033] Examples of preferred coating methods include a roll coater method, an air knife coater method, a blade coater method, a rod coater method, a reverse coater method, a bar coater method, a comma coater method, a die coater method, a gravure coater method, a screen coater method, a spray method, and a spinner method. From the viewpoint of versatility, the blade coater method and the bar coater method are preferred.
[0034] A coating film is obtained by the coating method. The coating film is dried to obtain the release layer 6. The release layer 6 is in close contact with the base layer 4.
[0035] A release layer 6 may be formed on a surface different from that of the base layer 4 by a coating method or the like. This release layer 6 is laminated on the base layer 4 via an adhesive layer. The adhesive layer may be formed from an adhesive or a pressure-sensitive adhesive. Examples of adhesives include urethane adhesives, acrylic adhesives, polyester adhesives, and polyamide adhesives. Examples of pressure-sensitive adhesives include rubber adhesives, acrylic adhesives, olefin adhesives, and silicone adhesives. The thickness of the adhesive layer is preferably 1 μm or more and 40 μm or less.
[0036] [Method of manufacturing membrane electrode assembly] An example of a method for manufacturing a membrane electrode assembly is shown in Figure 2. This manufacturing method includes forming an electrolyte membrane (STEP 1), forming a front-side catalyst layer (STEP 2), bonding (STEP 3), peeling (STEP 4), forming a back-side catalyst layer (STEP 5), bonding (STEP 6), and peeling (STEP 7).
[0037] In the formation of the electrolyte membrane (STEP 1), first, the resin of the electrolyte membrane is dissolved in a solvent to obtain a first coating liquid. Preferred solvents include water, alcohols such as methanol, ethanol, isopropanol, and 1-butanol, ketones such as acetone and methyl ethyl ketone, ethers such as dioxane and tetrahydrofuran, and sulfoxides such as dimethyl sulfoxide.
[0038] This first coating liquid is coated onto the release layer 6 of the release film 2 (first release film) shown in Figure 1. Preferred coating methods include a roll coater method, an air knife coater method, a blade coater method, a rod coater method, a reverse coater method, a bar coater method, a comma coater method, a die coater method, a gravure coater method, a screen coater method, a spray method, and a spinner method. A coating film is obtained by coating.
[0039] This coating film is heated. The heating temperature is preferably 80°C or higher and 200°C or lower, and particularly preferably 100°C or higher and 150°C or lower. The coating film is dried by heating, and the electrolyte membrane 16 shown in FIG. 3 is obtained. Drying may be performed at room temperature. This electrolyte membrane 16 is in close contact with the first release film 2a. The back side 18 of the electrolyte membrane 16 is in contact with the first release film 2a. The front side 20 of the electrolyte membrane 16 is exposed.
[0040] The first release film 2a and the electrolyte membrane 16 constitute a first laminate 22a. This first laminate 22a is wound around a reel. A first roll is formed by the winding. This first roll has multiple turns of the first laminate 22a. In this first roll, the first release film 2a with different turns abuts against the front side surface 20 of the electrolyte membrane 16. The first roll is stored for a predetermined period of time.
[0041] In the formation of the front catalyst layer (STEP 2), first, the resin of this catalyst layer is dissolved in a solvent to obtain a second coating liquid. The preferred solvent is the same as that described above for the first coating liquid. This second coating liquid is coated onto the release layer 6 (see FIG. 1) of the second release film 2b. In this embodiment, the specifications of the second release film 2b are the same as those of the first release film 2a. The preferred coating method is the same as that described above for the first coating liquid. A coating film is obtained by coating.
[0042] This coating film is heated. The heating temperature is preferably 50°C or higher and 150°C or lower, and particularly preferably 60°C or higher and 120°C or lower. The coating film is dried by heating, and the front catalyst layer 24 shown in Fig. 3 is obtained. Drying may be performed at room temperature. This front catalyst layer 24 is in close contact with the second release film 2b. The front side surface 26 of the front catalyst layer 24 is in contact with the second release film 2b. The back side surface 28 of the front catalyst layer 24 is exposed.
[0043] The second release film 2b and the front catalyst layer 24 constitute a second laminate 22b. This second laminate 22b is wound around another reel. A second roll is formed by the winding. This second roll has multiple revolutions of the second laminate 22b. In this second roll, the second release film 2b with a different revolution abuts against the back surface 28 of the front catalyst layer 24. The second roll is stored for a predetermined period of time.
[0044] In the bonding (STEP 3), the first laminate 22a is unwound from the first roll. Since the first release film 2a has excellent adhesion to the electrolyte membrane 16, blocking during unwinding can be suppressed even if the surface of the first release film 2a is smooth. In other words, the electrolyte membrane 16 does not adhere to the first release film 2a of a different turn. In the bonding (STEP 3), the second laminate 22b is further unwound from the second roll. Since the second release film 2b has excellent adhesion to the front catalyst layer 24, blocking during unwinding can be suppressed even if the surface of the second release film 2b is smooth. In other words, the front catalyst layer 24 does not adhere to the second release film 2b of a different turn.
[0045] The back surface 28 of the front catalyst layer 24 of this second laminate 22b is mated with the front surface 20 of the electrolyte membrane 16 of the first laminate 22a. This results in a laminate including the first release film 2a, the electrolyte membrane 16, the front catalyst layer 24, and the second release film 2b. This laminate is also called an intermediate laminate.
[0046] This intermediate laminate is heated and pressurized. The heating temperature is preferably 80°C to 200°C, more preferably 100°C to 180°C, and particularly preferably 110°C to 150°C. The pressing pressure is preferably 0.1 MPa to 20 MPa, more preferably 0.5 MPa to 15 MPa, and particularly preferably 1 MPa to 10 MPa. By heating and pressing, the front catalyst layer 24 is firmly adhered to the electrolyte membrane 16. As described above, each release film 2 has a base layer 4 that is flexible and does not easily stretch. Furthermore, this release film 2 includes a release layer 6 that has a suitable adhesion to the ion exchange resin layer. Therefore, in the heating and pressing process, unintended peeling of the first release film 2a from the electrolyte membrane 16 can be suppressed. Furthermore, unintended peeling of the second release film 2b from the front catalyst layer 24 can be suppressed.
[0047] In peeling (STEP 4), the first release film 2a is peeled off from the electrolyte membrane 16. The peeling exposes the rear side surface 18 of the electrolyte membrane 16. As described above, the surface of the release layer 6 is smooth. Therefore, the rear side surface 18 of the electrolyte membrane 16 can be made smooth.
[0048] In the formation of the backside catalyst layer (STEP 5), first, the resin of this catalyst layer is dissolved in a solvent to obtain a third coating liquid. The preferred solvent is the same as that described above for the first coating liquid. This third coating liquid is coated onto the release layer 6 (see FIG. 1) of the third release film 2c. In this embodiment, the specifications of the third release film 2c are the same as those of the first release film 2a. The preferred coating method is the same as that described above for the first coating liquid. A coating film is obtained by coating.
[0049] This coating film is heated. The preferred heating temperature is the same as that described above for the second coating liquid. The coating film is dried by heating, and the back-side catalyst layer 30 shown in FIG. 3 is obtained. Drying may be performed at room temperature. This back-side catalyst layer 30 is in close contact with the third release film 2c. The back side surface 32 of the back-side catalyst layer 30 is in contact with the third release film 2c. The front side surface 34 of the back-side catalyst layer 30 is exposed.
[0050] The third release film 2c and the back-side catalyst layer 30 constitute a third laminate 22c. This third laminate 22c is further wound around another reel. A third roll is formed by the winding. This third roll has multiple revolutions of the third laminate 22c. In this third roll, the front side surface 34 of the back-side catalyst layer 30 abuts against the third release film 2c of a different revolution. The third roll is stored for a predetermined period of time.
[0051] In the bonding step (STEP 6), the third laminate 22c is unwound from the third roll. Since the third release film 2c has excellent adhesion to the catalyst layer, blocking during unwinding can be suppressed even if the surface of the third release film 2c is smooth. In other words, the backside catalyst layer 30 does not adhere to the third release film 2c that is wound around a different circumference.
[0052] The front side 34 of the backside catalyst layer 30 of this third laminate 22c is aligned with the backside side 18 of the electrolyte membrane 16. This results in a laminate including the third release film 2c, the backside catalyst layer 30, the electrolyte membrane 16, the frontside catalyst layer 24, and the second release film 2b. This laminate is heated and pressurized. The heating temperature is preferably 80°C or higher and 200°C or lower, more preferably 100°C or higher and 180°C or lower, and particularly preferably 110°C or higher and 150°C or lower. The pressurizing pressure is preferably 0.1MPa or higher and 20MPa or lower, more preferably 0.5MPa or higher and 15MPa or lower, and particularly preferably 1MPa or higher and 10MPa or lower. By heating and pressing, the backside catalyst layer 30 is firmly adhered to the electrolyte membrane 16. As described above, each release film 2 has a base layer 4 that is flexible and difficult to stretch. Furthermore, this release film 2 includes a release layer 6 that has a suitable adhesion to the ion exchange resin layer. Therefore, in the heating and pressurizing process, unintended peeling of the second release film 2b from the front-side catalyst layer 24 can be suppressed. Furthermore, unintended peeling of the third release film 2c from the back-side catalyst layer 30 can be suppressed.
[0053] In the peeling step (STEP 7), the second release film 2b is peeled off from the front catalyst layer 24, and the third release film 2c is peeled off from the back catalyst layer 30. By these peeling steps, a laminate consisting of the back catalyst layer 30, the electrolyte membrane 16, and the front catalyst layer 24 is obtained. A gas supply layer and the like are further laminated on this laminate to obtain a membrane electrode assembly. As described above, the back side surface 18 of the electrolyte membrane 16 is smooth. Therefore, the back catalyst layer 30 is firmly bonded to the electrolyte membrane 16. This bonding contributes to the long life of the membrane electrode assembly.
[0054] The specifications of the second release film 2b may be different from those of the first release film 2a. The specifications of the third release film 2c may be different from those of the first release film 2a. EXAMPLES
[0055] The effects of the examples will be explained below, but the scope of the present specification should not be construed as being limited based on the description of these examples.
[0056] [Example 1] A coating liquid was obtained by dissolving 10% by mass of atactic polystyrene ("G100C", Toyo Styrene Co., Ltd.) in 90% by mass of toluene. On the other hand, a polyester film with an easy-adhesion layer ("Cosmoshine (registered trademark) A4100", Toyobo Co., Ltd.) was prepared as a base layer. The thickness of this polyester film was 50 μm, and the surface roughness Sa was 6 nm. The coating liquid was applied to the surface of the easy-adhesion layer of this polyester film with a wire bar #10 to obtain a coating film. This coating film was kept at a temperature of 100° C. for 1 minute and dried to obtain a release film of Example 1.
[0057] [Example 2] A release film of Example 2 was obtained in the same manner as in Example 1, except that a polyester film ("Lumirror (registered trademark) T60", Toray Industries, Inc.) was used as the base layer. This polyester film had a thickness of 75 μm and a surface roughness Sa of 13 nm.
[0058] [Example 3] The release film of Example 3 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10% by mass of atactic polystyrene ("G200C", Toyo Styrene Co., Ltd.) in 90% by mass of toluene.
[0059] [Example 4] The release film of Example 4 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10% by mass of atactic polystyrene ("G320C", Toyo Styrene Co., Ltd.) in 90% by mass of toluene.
[0060] [Example 5] The release film of Example 5 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10 mass % of atactic polystyrene ("H350", Toyo Styrene Co., Ltd.) in 90 mass % toluene.
[0061] [Example 6] The release film of Example 6 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10% by mass of atactic polystyrene ("H485", Toyo Styrene Co., Ltd.) in 90% by mass of toluene.
[0062] [Comparative Example 1] A release film of Comparative Example 1 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10 mass % of a cyclic olefin resin ("TOPAS-6015", Polyplastics Co., Ltd.) in 90 mass % toluene.
[0063] [Comparative Example 2] A release film of Comparative Example 2 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10 mass % of a cyclic olefin resin ("ZEONEX480R", Zeon Corporation) in 90 mass % toluene.
[0064] [Comparative Example 3] A release film of Comparative Example 3 was obtained in the same manner as in Example 1, except that a coating liquid was obtained by dissolving 10 mass % of a cyclic olefin resin ("ARTONF3500", JSR Corporation) in 90 mass % toluene.
[0065] [Comparative Example 4] The release film of Comparative Example 4 was obtained in the same manner as in Example 1, except that 10% by mass of a polyarylate resin ("UNIFINER M-2040", Unitika Ltd.) was dissolved in a mixture of 70% by mass of toluene and 20% by mass of methyl ethyl ketone to obtain a coating liquid.
[0066] [Comparative Example 5] A release film of Comparative Example 5 was obtained in the same manner as Comparative Example 1, except that a polyester film ("Lumirror (registered trademark) T60", Toray Industries, Inc.) was used as the base layer. This polyester film had a thickness of 75 μm and a surface roughness Sa of 12 nm.
[0067] [Comparative Example 6] A release film of Comparative Example 6 was obtained in the same manner as in Comparative Example 1, except that a polyester film (Diafoil (registered trademark) T100, Mitsubishi Chemical Corporation) was used as the base layer. This polyester film had a thickness of 75 μm and a surface roughness Sa of 36 nm.
[0068] [Comparative Example 7] A commercially available resin film ("HN-200", Kurabo Industries, Ltd.) was prepared as the release film of Comparative Example 7. The material of this resin film was syndiotactic polystyrene. The thickness of this resin film was 35 μm, and the surface roughness Sa was 72 nm.
[0069] [blocking] An ion exchange resin solution ("Nafion (registered trademark) 20 dispersion Solution DE2020CS type", DuPont) was prepared as the coating liquid. This coating liquid was applied onto the release layer of the release film to obtain a coating film. This coating film was held at a temperature of 100 ° C for 3 minutes to obtain a laminate of the release film and the ion exchange resin layer. The thickness of the ion exchange resin layer was 10 μm. Two test pieces were cut out from this laminate. The size of each test piece was 10 cm × 15 cm. The release film of one test piece was abutted against the ion exchange resin layer of the other test piece. A roller with a load of 2 kgf was passed over these test pieces twice to apply pressure. These test pieces were held in an environment with a temperature of 23 ° C and a humidity of 65% Rh for 24 hours. One test piece was peeled off from the other test piece in a time of 0.5 to 1.0 seconds. The condition of one of the test pieces was visually observed and rated according to the following criteria. A: The ion exchange resin layer was largely peeled off from the release film. B: The ion exchange resin layer was slightly peeled off from the release film. C: The ion exchange resin layer was not peeled off from the release film at all. The results are shown in Tables 1 and 2 below.
[0070] [Peeling force] An ion exchange resin solution (Nafion (registered trademark) DS2020CS, DuPont) was prepared as the coating liquid. The solid content of this ion exchange resin solution was 21% by mass ± 1% by mass. This coating liquid was applied onto a release film using a Mayer bar to obtain a coating film. This coating film was held at a temperature of 100°C for 3 minutes and dried. This coating film was further subjected to a heat treatment at a temperature of 160°C for 30 minutes to obtain a laminate of a release film and an ion exchange resin layer. The thickness of the ion exchange resin layer was 4 μm. A test piece was cut out from this laminate. In this test piece, the ion exchange resin layer was peeled off from the release film, and the peel force was measured. The conditions were as follows. Equipment: Autograph "AGS-X", Shimadzu Corporation Test piece width: 25mm Angle: 180° Speed: 600mm / min The results are shown in the following Tables 1 and 2. In the release films of Comparative Examples 3 and 4, the ion exchange resin layers were not peeled off.
[0071] [Easy to handle] A test piece identical to the test piece used for measuring the peel strength was prepared. This test piece was subjected to a heat treatment. The surface of this test piece was visually observed and ranked according to the following criteria. A: There are creases. B: There are some creases. C: No creases were observed. The results are shown in Tables 1 and 2 below.
[0072] [Table 1]
[0073] [Table 2]
[0074] As is clear from Tables 1 and 2, the release films of the examples are excellent in various performances. From these evaluation results, the superiority of this release film is clear.
[0075] [Disclosure items] Each of the following sections discloses a preferred embodiment.
[0076] [Item 1] The adhesive sheet includes a base layer and a release layer laminated on the base layer, The main material of the base material layer is polyester, The release layer comprises atactic polystyrene; A release film used in the manufacture of membrane electrode assemblies.
[0077] [Item 2] 2. The release film according to item 1, wherein the surface of the release layer has a water contact angle of 92° or less.
[0078] [Item 3] 3. The release film according to item 1 or 2, wherein the thickness of the release layer is 0.1 μm or more and 5 μm or less.
[0079] [Item 4] 4. The release film according to any one of items 1 to 3, wherein the average roughness Sa of the back side of the base material layer is 20 nm or less.
[0080] [Item 5] (1) A step of forming an electrolyte membrane on a surface of a first release film, the first release film including a base layer and a release layer laminated on the base layer, the base layer being mainly made of polyester, and the release layer including atactic polystyrene, to obtain a first laminate; (2) winding the first laminate to obtain a roll; (3) A step of forming a catalyst layer on the surface of a second release film to obtain a second laminate; (4) unwinding the first laminate from the roll and bonding the catalyst layer to the electrolyte membrane to obtain an intermediate laminate; and (5) A step of heating and pressing the intermediate laminate The method for producing a membrane electrode assembly comprising the steps of:
[0081] [Item 6] Item 6. The manufacturing method according to item 5, wherein in the step (1), the electrolyte membrane is formed on the surface of the first release film, which has an average roughness Sa of the back side of the first release film or less and a release layer having a thickness of 0.1 μm or more and 5 μm or less.
[0082] [Item 7] (1) A release film having a base layer and a release layer laminated on the base layer, the main material of the base layer being polyester, and the release layer containing atactic polystyrene; and (2) An electrolyte membrane laminated on the release film A laminate comprising: [Industrial Applicability]
[0083] The release film described above is suitable for producing various molded articles made of ion exchange resins. [Explanation of symbols]
[0084] 2. Release film 2a: First release film 2b: Second release film 2c...Third release film 4...Base material layer 6...Release layer 8...Dorsal surface of base layer 10....Front side surface of base layer 12....Back side of release film 14...Front side of release film 16...Electrolyte membrane 18. Back surface of electrolyte membrane 20...Front side of electrolyte membrane 22a...First laminate 22b...Second laminate 22c Third laminate 24... Front catalyst layer 26...Front side of front catalyst layer 28....Back surface of front catalyst layer 30...Back catalyst layer 32....Back surface of back catalyst layer 34...Front side of rear catalyst layer
Claims
1. The adhesive sheet includes a base layer and a release layer laminated on the base layer, The main material of the base material layer is polyester, The release layer comprises atactic polystyrene; A release film used in the manufacture of membrane electrode assemblies.
2. 2. The release film according to claim 1, wherein the surface of the release layer has a water contact angle of 92° or less.
3. The release film according to claim 1 or 2, wherein the release layer has a thickness of 0.1 μm or more and 5 μm or less.
4. The release film according to claim 1 or 2, wherein the average roughness Sa of the back surface of the base material layer is 20 nm or less.
5. (1) A step of forming an electrolyte membrane on a surface of a first release film, the first release film including a base layer and a release layer laminated on the base layer, the base layer being mainly made of polyester, and the release layer including atactic polystyrene, to obtain a first laminate; (2) winding the first laminate to obtain a roll; (3) A step of forming a catalyst layer on the surface of a second release film to obtain a second laminate; (4) unwinding the first laminate from the roll and bonding the catalyst layer to the electrolyte membrane to obtain an intermediate laminate; and (5) A step of heating and pressing the intermediate laminate The method for producing a membrane electrode assembly comprising the steps of:
6. The manufacturing method according to claim 5, wherein in the step (1), the electrolyte membrane is formed on the surface of the first release film, the surface of which has an average roughness Sa of the back side of 20 nm or less and a release layer having a thickness of 0.1 μm or more and 5 μm or less.
7. (1) A release film having a base layer and a release layer laminated on the base layer, the base layer being mainly made of polyester, and the release layer containing atactic polystyrene; and (2) An electrolyte membrane laminated on the release film A laminate comprising:
Citation Information
Patent Citations
Laminated film
JP2011161749A
Laminate for fuel battery fabrication, manufacturing method thereof, and manufacturing method of fuel battery
JP2014175116A
Release film for use in the manufacture of electrolyte membranes or membrane electrode assemblies
JP2022540472A
Release film
WO2014045888A1
Mold release film and method for producing flexible printed circuit board
WO2018173683A1